Learning styles theory fails to explain learning and achievement: Recommendations for alternative approaches. (1st October 2017) - An, Donggun; Carr, Martha
Abstract: The purpose of this paper is to propose a multiple approaches to explaining and predicting individual differences in learning. First, this article briefly reviews critical problems with learning styles. Three major concepts are discussed: lack of a clear, explanatory framework, problems of measurement, and a failure to link learning styles to achievement. Next, this paper presents several alternative approaches to learning styles that do a better job of explaining how learning styles might predict achievement. Alternatives to learning styles include individual differences in verbal and visual skills, expertise and domain knowledge, self-regulation and inhibition, and perfectionism. For expertise and domain knowledge, knowledge representation and fluency are specifically discussed. It is recommended that the new approach that focuses on individual differences in learning be used by teachers. Highlights: This article briefly reviews critical problems with learning styles. This article presents a multiple approaches to explaining individual differences in learning. This approach will be based in research in educational psychology and cognition.